Nicotine addiction management following surgery: a quality improvement approach in the post anesthesia care unit. (14th March 2018) - Finegan, Barry A; Roblin, Daniel; Hammal, Fadi
Abstract: Quality problem: For smokers, hospital admission is accompanied by forced involuntary nicotine abstinence due to smoke-free site/grounds policies. An audit of patients admitted to our surgical wards revealed that identification of smoking status was inadequate and that nicotine addiction management (NAM) was infrequently offered. The project aimed to enhance both these metrics by initiating NAM in the post anesthesia care unit (PACU). Initial assessment: Out of 744 patients admitted to our PACU in August 2015, 54% had their smoking status documented. The 200 patients (27%) out of the 744 were smokers and only 50% were offered NAM before discharge. Choice of solution: PACU unit staff to determine the smoking status of every patient before discharge from the PACU (later changed to OR nursing staff) and, if a patient was identified as a smoker, to offer NRT (patch and mouth spray only) and initiate therapy prior to transfer of the patient to the ward. Implementation: Data about number of patients admitted, presence of documented smoking status, number of identified smokers, and number offered/accepted nicotine replacement therapy (NRT) were collected at baseline and thereafter quarterly. Engaging video education sessions addressed the education gaps highlighted in a needs assessment. Identification of smoking status was made part of preoperative checklist and NRT was made available in post-operative recovery room. Results: These interventions resulted in an increase in screening for tobacco use from 54% at baseline to 95% and the offer of NRT to smokers from 50 to 89%.